2016
DOI: 10.3389/fmicb.2016.01440
|View full text |Cite
|
Sign up to set email alerts
|

UV-B Radiation Stress Causes Alterations in Whole Cell Protein Profile and Expression of Certain Genes in the Rice Phyllospheric Bacterium Enterobacter cloacae

Abstract: Among the different types of UV radiation, UV-B radiation (280-315 nm) has gained much attention mainly due to its increasing incidence on the Earth’s surface leading to imbalances in natural ecosystems. This study deals with the effects of UV-B radiation on the proteome and gene expression in a rice phyllospheric bacterium, Enterobacter cloacae. Of the five bacteria isolated from rice leaves, E. cloacae showed the highest level of resistance to UV-B and total killing occurred after 8 h of continuous exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…UV‐B radiation causes the formation of dimers of cellular DNA. These lesions block DNA replication and RNA transcription, leading to cell death . UV‐A radiation mainly produces single‐ and double‐stranded breaks, alterations in proteins and induced ROS formation .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UV‐B radiation causes the formation of dimers of cellular DNA. These lesions block DNA replication and RNA transcription, leading to cell death . UV‐A radiation mainly produces single‐ and double‐stranded breaks, alterations in proteins and induced ROS formation .…”
Section: Resultsmentioning
confidence: 99%
“…These lesions block DNA replication and RNA transcription, leading to cell death . UV‐A radiation mainly produces single‐ and double‐stranded breaks, alterations in proteins and induced ROS formation . Additionally, it has been demonstrated that solar radiation can cause sublethal injuries to E. coli .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisms isolated under UV irradiation at the end of a growing season in Texas, United States, tended to show higher tolerance to UV, and predominant groups in peanut were Bacillus coagulans, Clavibacter michiganensis , and Curtobacterium flaccumfaciens ( Jacobs and Sundin, 2001 ). Large-scale analysis in a UV-B resistant bacteria group isolated from rice, Enterobacter cloacae , revealed broad changes in ROS and in the number and expression of proteins upon exposure to UV-B ( Kumar et al, 2016 ). Future studies in the function of these proteins, together with gene expression profiling, may further elucidate the mechanisms of phyllospheric bacteria resistance and adaptation to UV-B ( Matallana-Surget and Wattiez, 2013 ; Kumar et al, 2016 ).…”
Section: The Role Of Lightmentioning
confidence: 99%
“…Large-scale analysis in a UV-B resistant bacteria group isolated from rice, Enterobacter cloacae , revealed broad changes in ROS and in the number and expression of proteins upon exposure to UV-B ( Kumar et al, 2016 ). Future studies in the function of these proteins, together with gene expression profiling, may further elucidate the mechanisms of phyllospheric bacteria resistance and adaptation to UV-B ( Matallana-Surget and Wattiez, 2013 ; Kumar et al, 2016 ). Effects of UV light on bacterial diversity may as well impact other groups of microorganisms.…”
Section: The Role Of Lightmentioning
confidence: 99%